A case study on learning environment for autistic children - Almazar, Althea Ceriza I.; Buencamino, Lorena M. (2008.)
This study aims to determine how the physical spatial organization of the classroom will enable students with autism spectrum disorder to be familiar with their environment and aid in their learning. The objective of the study is to identify the spatial requirements of a learning environment for autistic children; the physical structure of a classroom for autistic children in terms of the layout and flexibility of the space in order to teach autistic students effectively and efficiently. A school for special children was the chosen sample for this research. The study employed a descriptive method based on the characteristics and needs of the users as well as the documentation of the existing site. Direct observations of the children in their classroom and ocular inspection of the learning environment was documented. Analysis of the results showed that the school currently employs a multi-function use of a tight space flexible enough to accommodate the activities of its students. However, while the existing classroom layout may be appropriate for the other students, it fails to address the need of autistic students to have a predictable, readable, well-organized and scheduled learning environment critical to the promotion of their development. It is therefore recommended that a permanent physical layout will offer progression and efficiency that will aid in the autistic children's learning.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Autistic children -- Philippines; Classrooms -- Philippines